PEMANFAATAN ECENG GONDOK MENJADI PUPUK KOMPOS DI DANAU TOBA UNTUK MENINGKATKAN EKONOMI MASYARAKAT - Romauli Romauli; Sri Wahyuni Siregar; Abdurrozzaq Hasibuan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Within the caldera of a supervolcano in Indonesia, there is a large natural lake called Lake Toba. This is the largest lake in Southeast Asia. Although Lake Toba is touted by the President of the Republic of Indonesia as Asia's Monaco, its beauty is diminishing due to the rapid growth of water hyacinth. Agriculture and fisheries are the main source of income for local residents in Lake Toba. the main source of income for a family in agriculture, especially with the development of rice fields. The objective of the PKM was to assist the local community in converting Lake Toba water hyacinth into useful organic fertilizer. As a result, efforts were made to utilize this wild plant to make compost fertilizer that is full of benefits. The program consisted of three main activities, namely socialization, counseling, and practice of making compost fertilizer. The villagers who participated in the service activities were very active in participating during the activities, so that after participating in this activity, they had the knowledge and skills on how to make compost fertilizer from water hyacinth. Compost that has been physically decomposed is ready to be used as compost after 21 days, according to the technique of making compost using EM4 activator. At 21 days of observation, the treatment without EM4 bioactivator has not shown the physical characteristics of mature compost. It is expected that the community can make compost independently from water hyacinth which is widely available around the rice fields after this service project is completed. The compost can be sold to increase family income or used to meet fertilizer needs for farmers in their agricultural activities.